PELAKSANAAN PELATIHAN CALON INSTRUKTUR SENAM AEROBIK DI KOTA SEMARANG - Setiawan, Ipang (Universitas Negeri Semarang, 2010)
Training is one of ditermining factors of the success of an action plan. Traininghas also an important and strategic role in the development and growth of students.The focus of the study are: (1) the training for aerobic instructor candidates in threegyms in Semarang: St Anna Gym, Astuti Aerobic Dance, and Dian Ida Gunawan, (2)the factors affecting the training of aerobic instructor candidates in the three gyms.The research is aimed at understanding, identifying, and describing: (1) the executionof training for aerobic instructor candidates in the three gyms (2) the factors whichinfluence the training for aerobic instructor candidates in the three gyms. Theapproach of the study was phenomenological. Therefore, the research adopted aqualitative method. The data collected were words and pictures. The findings are asfollows: a) The trainer had knowledge and experience in his/her field, had a nationallevel certificate, attended gymnastic educations, atttended in-house training, attendedseminars in the level of general, local, or national, b) the trainees were not limited to aparticular age group, c) the written curriculum referred to the right guidelineaccording to the curriculum of gymnastics education, d) the training programs wereexecuted although they were not planned well. The existing training programs werenot recorded in writing and were still a routine, e) physical and mental training wascarried out. There were also additional methods such as aerobic assessment andestablishment although they were not written well, f) evaluation to the training wascarried out although it was not followed up well as a basis of improvement ofcontinuous training program.kata kunci: pelatihan, instruktur senam aerobik, senam aerobik